A Robust Algorithmic Framework for the Evaluation of World Happiness Ranking Based on Q Rung Orthopair Triangular Fuzzy Neutrosophic Set With Possibility Setting (PQ-RTFNS) - Saeed, Muhammad; Inam Ul Haq, Hafiz; Ali, Mubashir; Mustafa, Mudassira (Yugoslav Journal of Operations Research, 2025)
This paper presents a robust algorithmic framework for evaluating and ranking world happiness using a novel model based on q-rung orthopair triangular fuzzy neutrosophic sets (PQ-RTFNs) in a possibility setting. Traditional methods of ranking countries by happiness often face challenges in handling the complexity and uncertainty of the various social, economic, and environmental factors that influence well-being. To address this, the authors integrate the flexible and powerful PQ-RTFN model, which allows for better representation of indeterminate and inconsistent data. This approach enhances decision-making accuracy by effectively managing the fuzziness and ambiguity inherent in world happiness metrics. Through a comprehensive evaluation, the proposed framework demonstrates improved performance in ranking nations compared to existing models, offering a more reliable tool for policymakers and researchers to assess global happiness indices.